Patients' views of a pharmacist-run medication review clinic in general practice - Petty, Duncan R; Knapp, Peter; Raynor, D K; House, Allan O (British journal of general practice, 2003)
Reviewing elderly patients' medication is a requirement of the National Service Framework for Older People. Many general practitioners have insufficient time to review patients' medications in a consultation. Pharmacist review has been offered as an alternative and this will be a new experience for many patients. To ascertain patients' views of a pharmacist-conducted medication review clinic, run in their general practice surgery. Qualitative study using focus group interviews. General practices in Leeds Health Authority area. Patients aged 65 years and over, who had attended a medicine review clinic, took part in focus groups that were recorded and transcribed. Units of information representing an idea were identified and similar ideas were grouped together as themes. Patients had a number of prior beliefs about the clinic. Most patients knew that the clinic's purpose was to review repeat medication, to find out more about their medicines, and to ask questions about efficacy and side effects. Some patients were suspicious about the purpose of the clinic but others welcomed the opportunity to have an in-depth review and an explanation of their condition and its treatment; some patients did not accept advice or were disappointed that their expectations were not fulfilled. Most patients were happy to attend a yearly review but some expressed guilt about attending the surgery too frequently. Patients who attended the medication review clinics expressed a range of views about the service. Further research into patients' and carers' opinions about medicine review is needed to inform the development of these services.